2018
DOI: 10.1055/a-0586-4711
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Perspectives on Chia Seed and Its Oil: A Review

Abstract: The attraction of novel foods proceeds alongside epidemic cardiovascular disease, diabetes, obesity, and related risk factors. Dieticians have identified chia (Salvia hispanica) as a product with a catalog of potential health benefits relating to these detriments. Chia is currently consumed not only as seeds, but also as oil, which brings about similar effects. Chia seeds and chia seed oil are used mainly as a food commodity and the oil is also used popularly as a dietary ingredient used in various dietary sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 43 publications
2
43
0
2
Order By: Relevance
“…This study explored the effects of the long-term administration of chia seeds, a promising functional plant food with therapeutic perspectives [ 4 , 5 , 6 , 7 , 8 , 9 ], compared with a conventional diet in an experimental model of Sprague-Dawley rats. Male Sprague-Dawley rats fed a conventional diet tend to increase their bodyweight and reach a plateau of growing at around 12 months of life [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study explored the effects of the long-term administration of chia seeds, a promising functional plant food with therapeutic perspectives [ 4 , 5 , 6 , 7 , 8 , 9 ], compared with a conventional diet in an experimental model of Sprague-Dawley rats. Male Sprague-Dawley rats fed a conventional diet tend to increase their bodyweight and reach a plateau of growing at around 12 months of life [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dietary n -6/ n -3 ratio has been a topic of great interest, because recent evidence suggests that a high n -6/ n -3 ratio is associated with higher risk of several diseases [ 58 , 59 ]. The health benefits of n -3 ALA have been highlighted in different studies owing to its potential effect for the prevention of cardiovascular diseases, fracture risk, obesity, and other obesity-associated disorders, such as diabetes [ 4 , 60 , 61 ]. A recent investigation in animals prone to diabetes found that the intake of chia seeds rich in n-3 ALA was able to reduce blood levels of pro-inflammatory cytokines and ameliorate insulin sensitivity [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The applicants provided eight articles on human studies (Nieman et al, 2009Vuksan et al, 2010Vuksan et al, , 2017aIllian et al, 2011;Guevara-Cruz et al, 2012;Jin et al, 2012;Ho et al, 2013) and three reviews (Ulbricht et al, 2009;Ali et al, 2012;Teoh et al, 2018). EFSA retrieved six additional human studies in literature search (Brissette et al, 2013;Toscano et al, 2014Toscano et al, , 2015Nieman et al, 2015;Ayaz et al, 2017;Vuksan et al, 2017b) and three review articles (De Souza Ferreira et al, 2015;Parker et al, 2018;Grancieri et al, 2019).…”
Section: Toxicological Informationmentioning
confidence: 99%
“…These secondary metabolites show therapeutic effects by acting as analogs to various endogenous metabolites like, hormones, ligands, signaling molecules or neurotransmitters [13]. As a matter of fact herbal medicines possess multiple therapeutic properties [14] show little or negligible side effects or toxicity. With the advent of modern drugs, there has been a decrease in the use of herbal medicines for some time but interestingly, the trend has changed now.…”
Section: Introductionmentioning
confidence: 99%